The Family Function and Depression on Junior High School Students: Does Emotional Regulation Mediate? - Hasanuddin; Rahmi Lubis; Nabila Agnil Alivia; Christen Natalia; Nasywa Fitri Aswali Dhiya; Roza Noviardhana Hidayat; Aldira Aulia Muhaimin (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
Junior high school students are in early adolescence, where sexual hormones are active and provoke emotional instability. Pubertal life challenges cause adolescents susceptible to depression. One of the factors that causes depression is family function. However, the influence of family function with depression is inconclusive. The capability to regulate their emotions determines adolescent depression levels. This study aims to examine the role of emotional regulation in mediating the influence of family function on depression levels in junior high school students. Three hundred and one junior high school students in Medan filled out the family function scale, emotional regulation scale, and Beck Depression Inventory-II. Data analysis using a mediation test with the Jamovi statistical software Version 4.2 showed that emotional regulation did not significantly mediate family function on depression. Family function directly affects depression levels in junior high school students. Family function impacts emotional regulation and emotional regulation influences depression levels. The results of the study are beneficial in compiling intervention programs to decrease students' depression levels by focusing on strengthening family function